Communicating health risks to the public : a global perspective - Hillier, Dawn, 1950- (Gower, 2006)
This book reviews current health risk communication strategies, and describes the techniques, including drama, storytelling and scenarios that are used to identify and prioritise key communication issues, and to identify policy responses. The book also.